1000x=(1000x-1x)

Simple and best practice solution for 1000x=(1000x-1x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1000x=(1000x-1x) equation:


Simplifying
1000x = (1000x + -1x)

Combine like terms: 1000x + -1x = 999x
1000x = (999x)
1000x = (999x)

Solving
1000x = (999x)

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '(-999x)' to each side of the equation.
1000x + (-999x) = (999x) + (-999x)

Combine like terms: 1000x + (-999x) = 1x
1x = (999x) + (-999x)

Combine like terms: (999x) + (-999x) = 0
1x = 0

Divide each side by '1'.
x = 0

Simplifying
x = 0

See similar equations:

| 3m+g=2k | | 0.4y+0.7=0.2-0.1y | | -2k-3=19 | | 6x-5+1=-13 | | -7=-8 | | 198=90+x+5x | | 3x-([-5x]-11)=(-197) | | 5y+8=38 | | S=2(pie)rh | | 7(a+1)-3a=5+4(a-1)2 | | 2x+y=(-9) | | 66.6(6j+9)=3j+7 | | 7x=-1.60 | | -2(z+4)=-(z-5) | | 6(3n+4)=7(8n+4)+7 | | 3a+12=343 | | x-8-2(x+1)=-10 | | -2(3t-4)+4t=8t-9 | | 6(x-15)=3(14+x) | | 2(x+2)-4x=5(x-1) | | 3w-5(w-6)=2(10-w) | | 2(x+6)+(x+2)(x-2)=2x+8 | | X-90=8x | | 3x-4x=2x+25 | | -5(1-2m)-4m=23+2m | | -8x+41=-22 | | -5m+10=-10 | | 140-6x=462+10x | | 11x+13=15x-3 | | -0.45=0.03x+.015 | | 0.3x+4.3=0.2x+1.2 | | 140+10x=462-6x |

Equations solver categories